Operational monitoring of rainfall over the Arno River basin using dual-polarized radar and rain gauges - Scarchilli, G., author; Gorgucci, E., author; Chandrasekar, V., author; American Meteorological Society, publisher (Colorado State University. Libraries, 1996)
Reflectivity (ZH) and differential reflectivity (ZDR) measurements collected by Polar 55C over the Amo River basin in Italy are presented. The applicability of dual-polarization (ZDR)-based rainfall algorithms at C band in an operational setting is studied in conjunction with a network of rain gauges. Conventional pointwise comparison of radar and rain gauge estimates of rainfall, as well as statistical comparison of dual-polarization radar and rain gauge data via probability matching procedure, are presented. Error structure of reflectivity rainfall Z-R relation, as well as ZDR-based algorithms, is evaluated as a function of spatial and temporal averaging. Pointwise comparison, as well as statistical evaluation based on cumulative distribution function (CDF) matching, are used to show that in an operational environment with excessive ground-clutter contamination and attenuation problems the dual-polarization-based rainfall algorithm performs better than any arbitrary Z-R relation. In addition, it is shown that a dual-polarization (ZDR) algorithm obtained matching the CDFs performs better than the best possible Z-R relation.